Computer Aided Surgery - Fujie, Masakatsu (Springer Japan : Imprint: Springer, 2016)
This book presents the latest research advances in the theory, design, control, and application of robot systems intended for a variety of purposes such as manipulation, manufacturing, automation, surgery, locomotion, and biomechanics. Several chapters deal with fundamental kinematics in nature, including synthesis, calibration, redundancy, force control, dexterity, inverse and forward kinematics, kinematic singularities, and over-constrained systems. This book is a compilation of the extended versions of the very best papers selected from the many that were presented at the Asian Conference on Computer-Aided Surgery held September 16-18, 2013, in Tokyo, Japan (ACCAS 2013).